Partial discharge characteristics during electrical treeing in silicone rubber - Mohamed Shafarin Razi, 1979-, author 641662; Mohd. Hafizi Ahmad, supervisor 602156; Fakulti Kejuruteraan Elektrik 540663 (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2016)
Thesis (Sarjana Kejuruteraan (Elektrik - Kuasa))